KONTRIBUSI PT TANGERANG NUSANTARA GLOBAL TERHADAP PENDAPATAN ASLI DAERAH KOTA TANGERANG TAHUN 2020-2022 : Contribution of PT Tangerang Nusantara Global to the Regional Original Revenue of Tangerang in 2020-2022 - Muhammad Miftahuddin; Eko Primananda (Faculty of Law, Universitas Trisakti, 2024)
PT Tangerang Nusantara Global is one of the BUMDs formed by the Tangerang city government, as a means of resource management and efforts to optimize PAD potential.The formulation of the problem discussed is whether the contribution of BUMD PT Tangerang Nusantara Global to Tangerang City PAD for the 2020-2022 period is in accordance with Law no. 23 of 2014 concerning Regional Government and what obstacles the BUMD PT Tangerang Nusantara Global faces. The research method is descriptive, normative research type and uses literature studies, with conclusions using deductive logic. The results of the research and discussion are that PT Tangerang Nusantara Global contributes by obtaining two types of income, income originating from its business sector and income form of deposits. The obstacle faced is ownership of regional property (BMD) which is not yet fully held by PT Tangerang Nusantara Global. The conclusion is contribution of PT Tangerang Nusantara Global to the PAD of Tangerang City in 2020-2022 in accordance with Law no. 23 of 2014 concerning Regional Government. PT Tangerang Nusantara Global functions to support the regional economy, but its PAD contribution is not yet significant. More positive efforts are needed to be able to contribute more to the region